Generation of Substitution Box Structures Based on Blum Blum Shub Random Number Outputs - Ari, Ali; Ozkaynak, Fatih (Institute of Electrical and Electronics Engineers Inc., 2022)
One of the most important milestones in our transformation into a digital society is the effective adoption of Internet technologies by all stakeholders of the society. The critical factor in this adoption has been the trust model provided through cryptographic protocols. However, the secure environment that tries to be created with cryptographic algorithms is constantly under attack threat with technological developments. Therefore, it is necessary to develop new algorithms resistant to new attacks. In this study, a new approach is proposed for substitution box structures, which is a cryptographic component that can be used as a precaution against side channel attacks. The success of the obtained component has been analyzed for five basic substitution box design metrics. Successful experimental results indicate that the proposed approach have various potentials for new practical applications that can be designed in the future. © 2022 IEEE.
16th IEEE International Conference on Advanced Trends in Radioelectronics, Telecommunications and Computer Engineering, TCSET 2022 -- 22 February 2022 through 26 February 2022 -- Lviv-Slavske -- 179157
Keywords: Blum Blum Shub generator; chaotic map; randomness; substitution box